Perbedaan Lama Pelepasan Tali Pusat pada Metode Perawatan Tali Pusat Teknik Terbuka dan Tertutup di PMB “SF” Palangka Raya: Differences in the Delivery of the Course in the Open Engineering and Closed in PMB “SF” Palangka Raya - Bingan, Eline Charla Sabtina (Jurnal Surya Medika (JSM), 2021)
Tetanus neonatorum is a disease in neonates caused by Clostridium Tetani spores that enter through the umbilical cord. Various attempts were made to reduce infection in the umbilical cord, one of which is the method of treatment performed on the umbilical cord. This study aims to determine the differences in the old cord release in cord care with open and closed techniques in PMB SF Palangka Raya City. This research design is a descriptive quantitative analytic method with the approach of the type of research used is "True Experiment" real experimental research using observation sheets. The samples used were babies born in SF PMB with 26 babies; the sampling technique used was the non-probability sampling technique, purposive sampling, while the analysis used was Chi-Square. From the study results, it was found that there was a significant difference in the length of umbilical cord release in the umbilical cord treatment method with open and closed techniques with an Exact Sig. (2-tailed) value of 0.011. So the Exact Sig. Value (2-tailed) 0.011 <0.05, then Ho is rejected. And umbilical cord care with the open method is 19 times more effective at accelerating the release of the umbilical cord than the closed umbilical cord treatment method.